Osteogenesis Potential of Polymethylmethacrylate–Hydroxyapatite and Stem Cells from Human Exfoliated Deciduous Teeth as Alveolar Bone Graft: An InSilico Study - Saskianti, Tania; Angelina, Michelle; Dewi, Ardianti Maartina; Antonius, Yulanda; Zahri, Amelinda Nabila; Ridwan, Rini Devijanti; Kanawa, Masami; Kawamoto, Takeshi; Tanimoto, Kotaro; Fujimoto, Katsumi (European Journal of Dentistry, 2025)
The goal is to analyze the osteogenesis potential of polymethylmethacrylate (PMMA)–hydroxyapatite (HA) and stem cells from human exfoliated deciduous teeth (SHED) as a biomaterial candidate for alveolar bone defect therapy through a bioinformatic approach within an in silico study.Three-dimensional (3D) ligand structures consisting of HA, PMMA, and target proteins of SHED were obtained from the PubChem database. STITCH was used for SHED target protein analysis, STRING was utilized for analysis and visualization of protein pathways related to osteogenesis, PASS Online was employed to predict biological functions supporting osteogenesis potential, PyRx 0.8 was used for molecular docking analysis, and PyMol was utilized to visualize the 3D structures resulting from the molecular docking analysis.PMMA ligand was found to support osteogenesis through several biological functions, while interaction of HA ligand with matrix metalloproteinase (MMP) 20, DSPP, IBSP, SPP1, CD44, and MMP7 protein was revealed to play a role specifically in extracellular matrix organization. The interaction of all these proteins played a role in various pathways of osteogenesis. Toxicity level predictions of PMMA and HA were at class V and class III, respectively, which means that both ligands were shown to be neither hepatotoxic, carcinogenic, immunotoxic, nor cytotoxic. However, the ligand of PMMA had a lower binding affinity to SHED's protein (MMP7, MMP20, CD44, BMP7, and COL1A1) than the control ligand.The interaction between HA–PMMA ligands and several SHED proteins showed biological process and osteogenesis pathways supporting the osteogenesis potential of PMMA–HA and SHED for alveolar bone defect therapy.
Keywords: insilico; human and health; polymethylmethacrylate; hydroxyapatite; stem cells from human exfoliated deciduous teeth; alveolar bone defect therapy